DIRECTIVE SPEECH ACT IN THE CARTOON MOVIE OF RAYA AND THE LAST DRAGON - Hindriyani Gafur; Taib Latif; Sri Ayu Budi Lestari (Jurnal Bilingual, 2023)
This research discusses speech acts which are one of the basic elements in pragmatics. Speech acts consist of five categories, one of which is directive speech acts. This study aims to identify the types of directive speech acts contained in the cartoon film Raya and the last dragon, and also to determine the function of the directive speech acts used in the film. This study uses descriptive qualitative method in analyzing data. Data collection was carried out by reading film scripts and watching films to analyze the body movements, gestures and dialogues of each character. The results of the analysis show that there are eight types of directive speech acts found in the film, namely Question, Command, Advice, Asking, Entreating, Prohibiting, Permitting and Suggestion. Besides that, the general function of these types of directive speech act was found.